PENGARUH TERPAAN FACEBOOK SEBAGAI MEDIA MARKETING DAN PERSEPSI CALON KONSUMEN PADA KUALITAS PRODUK RUMAH SUBSIDI TERHADAP KEPUTUSAN PEMBELIAN RUMAH SUBSIDI PERUMAHAN TAPOS SEJUK KAB. SUKABUMI - Darda Putranto, Addakhil; Lestari, Sri Budi; Pradekso, Tandiyo (Interaksi Online, 2024)
Subsidized housing has become one of the programs facilitating individuals to own homes. West Java is the region with the highest demand for subsidized housing in Indonesia. This situation has led to an oversupply in the area. Additionally, almost all developers employ similar marketing and communication strategies on social media platforms. The issues surrounding marketing strategies and communication on social media are related to how marketing teams communicate their subsidized housing products, such as choosing the appropriate social media platform for the product and the form of communication, such as images, videos, and copywriting. This has resulted in competition among subsidized housing developers in West Java. The results indicate that there is no significant influence of Facebook exposure as a marketing medium on the decision to purchase subsidized housing in Perumahan Tapos Sejuk, Kab. Sukabumi. Furthermore, no significant influence was found between potential consumers' perceivced quality of subsidized housing products and the decision to purchase subsidized housing in Perumahan Tapos Sejuk, Kab. Sukabumi